Research and evaluation on growth and salinity toterance ability of rice line carrying saltol/qtl at the germination and seedling stages - Mai Hoa, Dieu Thi; Ham, Le Huy; Linh, Le Hung (Academia Journal of Biology, 2016)
In this study, we have evaluated the salinity tolerance levels of OM6976-Saltol line. This line was generated by introgressing the Saltol/QTL into elite OM6976 rice by marker assisted backcrossing (MABC). The carried Saltol/QTL of OM6976-Saltol line contains genetic characteristics and agro-biomophological variation that are the same as OM6979 except salt-tolerant gen. This experiment was conducted to evaluate germination ability of seeds in Yoshida nutrition containing concentration of NaCl at 50 mM, 100 mM, 150 mM, 200 mM and using 0 mM NaCl as positive control. Selection of artificial salt condition containing concentration of NaCl at 150mM to assess the growth ability of plants. By using the SES (Standar Evaluating Score) from IRRI, the salinity tolerance ability of OM6976-Saltol line was evaluated at 150mM NaCl. The result showed that OM6976-Saltol line has salt tolerance ability with 150mM NaCl at quite level (score 3) while the controlled OM6976 line was at sensitive level (score 7). OM6976-Saltol line has ability grown in salt conditions at germination and seedling significantly higher than OM6976.